The Effect of Fermentation on The Nutrients of Processed Cowpea (Vigna unguiculata l. Walp) - Cicik Lestari; Sugeng Maryanto; Riva Mustika Anugrah (UNIVERSITAS NGUDI WALUYO, 2021)
Cowpea is a type of legume in Indonesia but utilization not optimal. Cowpea can be used as a basic of making tempeh. The purpose of the study is to know the effect of fermentation on the nutrients of processed cowpea. The design of the study was Pra Eks/imen Design with Completely Randomized Design in laboratory to test nutrients which were repeated 3 times. Data analysis used SPSS (Statistical Product Service Solution) application. The measurement of carbohydrate used anthron method, crude fiber used refluks method, total protein used kjeldhal method, and fat used soxhlet method. Nutrients of boiled cowpea is carbohydrate content of 31,21%; crude fiber content of 13,94%; total protein content of 26,71% and fat content of 7,35%. Nutrients of cowpea tempeh is carbohydrate content of 26,71%; crude fiber content 17,21%; total protein content of 15,38% and fat content of 1,44%. There are not statistical different nutrients of boiled cowpea and tempeh cowpea, but different values